Fondò l’autonomia del diritto, non quella della politica - De Angelis, Massimo (B@belonline, 2024)
In the area of political philosophy, Immanuel Kant admirably established the distinction between “Right”(concerning man’s external liberty) and “Moral” (concerning man’s inner world). This distinction works both regarding the State as moral person founded on the “law”, and the international right and the relationships among the different States. Following this way Kant robustly founds the State as liberal, based on the “right”: neither an ethical State therefore nor a dispotic one. A republican and representative State different from a democratic one. His idea of perpetual peace has nothing to do with a utopia but is based on a strong realism. Kant nevertheless, has not managed to found the distinction between “Politics” and “Right”. This depends on his idea of “Reason”, pretty normative and not able to become “historical reason”. Nowadays, Kant’s ideas regarding international right are very popular again, after the decline of Marxism. But along this pattern we risk to overlook that only with a new and strong idea of politics and political autonomy we can deal and solve the dilemmas of the present time.